SELF-POWERED ELECTRONIC LOCK - HARVEY MICHAEL P (2010)
A self-powered electronic lock is provided having a housing, a lock element mounted in the housing for movement relative to the housing between a locked position and an unlocked position, a code input device operating with a first set of electronics, and an electric actuator operating with a second set of electronics. The electric actuator is operatively coupled with the lock element to allow movement of the lock element from the locked position to the unlocked position. A first electric power generator is operative by a user to supply electrical power for operating the code input device and the first set of electronics. A second electric power generator is operative to supply electrical power for operating the electric actuator and the second set of electronics. The first and the second set of electronics are electrically isolated and are synchronized to generate a common number for a combination code.